2018
DOI: 10.1097/pec.0000000000001545
|View full text |Cite
|
Sign up to set email alerts
|

Care Coordination in Emergency Departments for Children and Adolescents With Behavioral Health Conditions

Abstract: Background: Increasing numbers of children are receiving care for behavioral health conditions in emergency departments (EDs). However, studies of mental health-related care coordination between EDs and primary and/or specialty care settings are limited. Such coordination is important because ED care alone may be insufficient for patients' behavioral health needs. Methods:We analyzed claims during the year 2014 from Truven Health Analytics MarketScan Medicaid and Commercial databases for outpatient services an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…They noted, however, that follow-up with these adolescents is infrequent and that, even when outpatient services are offered, engagement after ED discharge is poor. An analysis of claims data in the U.S. from 2014 found that approximately 46% of individuals aged 2 to 18 seen in an ED with a psychiatric diagnosis had a follow-up visit with a primary care provider or a specialty mental health provider within 7 days of ED discharge (Lynch et al, 2021). Frosch et al (2011) examined repeat pediatric psychiatric ED visits in an urban general hospital to determine why youth were seeking care and if their ED visits led to increased outpatient connections.…”
Section: Connection To Outpatient Carementioning
confidence: 99%
“…They noted, however, that follow-up with these adolescents is infrequent and that, even when outpatient services are offered, engagement after ED discharge is poor. An analysis of claims data in the U.S. from 2014 found that approximately 46% of individuals aged 2 to 18 seen in an ED with a psychiatric diagnosis had a follow-up visit with a primary care provider or a specialty mental health provider within 7 days of ED discharge (Lynch et al, 2021). Frosch et al (2011) examined repeat pediatric psychiatric ED visits in an urban general hospital to determine why youth were seeking care and if their ED visits led to increased outpatient connections.…”
Section: Connection To Outpatient Carementioning
confidence: 99%
“…This study shows some of the factors that are associated with high levels of repeat ED visits made by youth with BH conditions from low income families. The implementation of medical homes (Monti & Rosner, 2015) and regular follow-up after an ED visit (Lynch et al, 2018) may support improvements in population health by improving access to BH care outside of the ED, possibly reducing ED visits by youth (Moore et al, 2016). Improvements in ED providers' access to community-based BH resources related to treatment of substance use and ADHD are urgently needed so that quality of care improves, health care costs are controlled, and youth experience fewer BH crises.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, few studies have measured prompt emergency department follow-up for patients with a mental disorder, and even fewer were longitudinal studies using diverse clinical administrative databases. 8 Most studies have evaluated specific populations, such as youth with mental disorders 9 and patients with depression, 5 mood disorders 10 or self-harm behaviours. 7 More prompt emergency department follow-up was identified among patients with serious mental disorders such as bipolar disorders 3 or those who engaged in self-harm; 7 unlike patients with depression, mood disorders 8 or substance-related disorders, 3 for whom follow-up was delayed.…”
mentioning
confidence: 99%
“…7 More prompt emergency department follow-up was identified among patients with serious mental disorders such as bipolar disorders 3 or those who engaged in self-harm; 7 unlike patients with depression, mood disorders 8 or substance-related disorders, 3 for whom follow-up was delayed. Women, 8,9 patients residing in areas other than medium-to-high poverty neighbourhoods 11 or urban areas, 12 patients integrated in out-patient programmes with low wait times 4 and those who previously used out-patient mental health services 13 also had greater access to prompt emergency department follow-up. However, prior service use as a predictor of prompt emergency department follow-up has been understudied, especially in terms of the type and intensity of services provided or continuity of care.…”
mentioning
confidence: 99%